Communication Patterns for Assistance to Muhafidz (BMTK) and Santri in Increasing Discipline in Memorizing the Qur'an at Ma'had Tahfidh Al-Amien - Agus Saifuddin Amin; Taufik Hasbulla Laisbuke (Maklumat: Journal of Da'wah and Islamic Studies, 2024)
The communication pattern of muhafidz assistance with students runs effectively and has different strategies in efforts to habituate student discipline. Where in the students they will interact with the Qur'an, where the communication pattern of a muhafidz will be used as a view and this will have an effect, this is where the role of muhafidz in carrying out the discipline of students in memorizing the Qur'an at Ma'had Tahfidh Al-Qur'an Al-Amien. The purpose of this study is to find out what communication patterns are used by muhafidz in carrying out the discipline of memorizing the Qur'an at Ma'had Tahfidh, and to find out what are the supporting and inhibiting factors of memorization methods in carrying out the discipline of memorizing the Qur'an at Ma'had Tahfidh. The method in this study uses qualitative descriptive case studies. Research results: the pattern used is the Dzatiya Da'wah Wheel Pattern and the Circle Communication Pattern / Da'wah Halaqah. The supporting factor is the existence of indicators that can determine whether or not the students' targets are achieved. The inhibiting factor is sleepiness and sleep when implementing halaqoh tasmi'